The Environmental Impact on Children’s Language Development - Naily Inayatul Maghfirah; Irfan Masrur (English Language Teaching Journal, 2025)
The environment is a factor that has a considerable influence on children’s language development. Because with the environment, they can continue the routine as well without feeling difficulties. The stimulation that a child gets through the environment influences the child's language development. Stimulation that is received slowly will affect the child's language development. The role of parents is very important in guiding and teaching children. The family is the first and foremost environment in child development. Parents really need to understand these steps. Development according to the age of a child's cognitive development will be able to influence his development, this is related to his success or delay in thinking and communicating with a child who is said to be slow in speaking can affect the ability to connect in everyday life personally or socially. So that children have no difficulty learning to socialize and other work activities when they grow up. Factors that can affect children's language development include the following: Brain development and intelligence, Gender, physical condition, Family environment, Economic conditions, Regional social/cultural settings, Bilingualism (2 languages). Keywords: the role of environment, children's Language development